THE EFFECT OF TEACHING MEDIA ON STUDENTS’ ACHIEVEMENT IN SPEAKING - Resti Santa Mona Sidabutar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2014)
This research concerned on The Effect of Teaching Media on Students’ Achievement in Speaking. This study used the experimental design. The population of the study was the students of SMP Negeri 1 Air Putih. There were twenty students from five classes as the sample of the research. This study was conducted with two groups namely experimental and control group. The experimental group was taught by applying English comics while control group was taught with written texts. The instrument of collecting the data was used tape recorder. The data was analyzed by using t-test formula. The calculation shows that t-observed (2.378) is higher than t-table (2.086) at the level of significance 0.05. Therefore, the null hypothesis is rejected and alternative hypothesis is accepted. It means that teaching speaking by applying English comics as the media has more significant effects than without using English comics.   Keywords: English Comics, Story Retelling, Students’ Achievement in Speaking, Experimental Research